Тирик организмларга таъсир кўрсатувчи экологик омилларни ўрганишда фанлар интеграцияси - Давлатова, C.Т (SCIENCE and SOCIETY, 2020)
The author described logically and consistently the integration of science into the study of environmental factors affecting living organisms.
Keywords: scientist; risk; abiotic; biotics; population; optimism; zone; consequence; anthropogenic; autropogenic